The study on the current inventory management activities in Celcom: efficiency measurement and its effectiveness / Shahrin Nasir - Nasir, Shahrin (2007)
Cellular Communication Network (Malaysia) Sdn. Bhd. (CELCOM) was established in 1988. It is one of the Technological Resources Industries (TRI) company. The commercial operations started in 1989. Celcom is the first company to provide the mobile telecommunications services in Malaysia. By providing services on 900 MHz frequency, ART 900 is the only service available until 1993. Since then Celcom has upgraded the ART 900 coverage to compete with new competitors. Due to that, more telecommunication sites have to be set up to provide wider coverage area for ART 900 services. As a result, effective inventory management has to be in tandem with the development. Before the site could be set, logistics will play its role first. Inventory management activities have to be efficient and effective, from receiving, storing and issuing the items to the site. Every thing starts from the warehouse, if items are not available, this will result in the site not being built. From the observation that, was made, the result showed that all the inventory management activities in Celcom created problems that give impact on the level of effectiveness in inventory management.